Hallucinogenic Persisting Perception Disorder: A Case Series and Review of the Literature - Ford, Hannah; Fraser, Clare L.; Solly, Emma; Clough, Meaghan; Fielding, Joanne; White, Owen; Van Der Walt, Anneke (Frontiers in Neurology, 2022)
Background Hallucinogen persisting perception disorder (HPPD) is characterized by the re-emergence of perceptual symptoms experienced during acute hallucinogen intoxication following drug cessation. The underlying pathophysiology is poorly understood. We report the clinical characteristics and investigation findings of a series of HPPD cases with a literature review of previous case reports. We draw parallels between the features of HPPD and VSS. Methods Retrospective case series of 13 patients referred from neuro-ophthalmologists. Literature review with 24 HPPD case reports were identified through database search using the terms “hallucinogenic persisting perception disorder” OR “hallucinogen persisting perception disorder”. Results Lysergic acid diethylamide (LSD), 3,4-Methyl enedioxy methamphetamine (MDMA) and cannabinoid use was common. Cannabinoids and MDMA were mostly used in association with classical hallucinogens. The most frequent symptoms in our patients were visual snow, floaters, palinopsia, photophobia and nyctalopia. In the literature other symptoms included visual hallucinations altered motion perception, palinopsia, tracers and colour enhancement. Ophthalmic and neurologic investigations were mostly normal. The majority of patients had ongoing symptoms. Two of our patients fully recovered – one after treatment with benzodiazepine and one without treatment. 25% of cases from the literature fully recovered. Conclusions HPPD presents with heterogeneous visual phenomena on a background of previous classic and non-classic hallucinogen use. Ophthalmic investigations are typically normal. The symptoms of HPPD in our case series overlap with the typical features of Visual Snow Syndrome (VSS). Patients presenting with VSS should be screened for past recreational drug use. The DSM-5 description of HPPD does not include visual snow, nyctalopia, photophobia or floaters. A revision of the diagnostic criteria to include these symptoms may better reflect the typical clinical phenotype. Increased awareness of HPPD as a secondary cause of VSS can avoid extensive investigations. Controlled trials comparing primary and secondary VSS patients are needed to understand the pathophysiology better and optimize treatment for HPPD.